Área foliar remanescente, boro, zinco e sacarose na produção de mudas de Coffea arabica L. por miniestaquia - Honda Filho, Cássio Pereira (2022)
Mini cuttings can be considered a specialization of conventional cuttings. It basically consists of the use of shoots from plants propagated by the cutting process, or seedlings produced by seeds. In addition, it may represent a potentially viable alternative for woody species whose conventional cutting process results in variable rooting percentage and poor quality in root formation, as is the case of the species Coffea arabica L. The objective was to evaluate the influence of boron, zinc, sucrose and the remaining leaf area in the rooting of minicuttings of Coffea arabica L. Two experiments were then carried out in a completely randomized design, arranged in a triple factorial 2x3x3, as follows: presence or absence of boron (experiment 1) or zinc (experiment 2 ) in the rooting solution with AIB; sucrose at 0, 10 and 20% concentration applied every 20 days; levels of remaining leaf area on minicuttings (25, 50 and 75%). In both experiments it was noted that the presence of B and Zn were efficient for good root growth; the increase in sucrose concentration in the spraying solution was beneficial for root growth in both experiments; treatments with 75% of remaining leaf area were superior to the other treatments. It is concluded that the current protocol for rooting arabica coffee minicuttings should be expanded with addition of B or Zn in the solution with AIB; use of exogenous sucrose doses at 20% concentration in an interval of 20 days; option of maintaining a higher percentage of the remaining leaf area for a more efficient and homogeneous rooting of minicuttings.